2023
DOI: 10.1111/nph.19094
|View full text |Cite
|
Sign up to set email alerts
|

An extracellular β‐N‐acetylhexosaminidase of Medicago truncatula hydrolyzes chitooligosaccharides and is involved in arbuscular mycorrhizal symbiosis but not required for nodulation

Abstract: Summary Establishment of symbiosis between plants and arbuscular mycorrhizal (AM) fungi depends on fungal chitooligosaccharides (COs) and lipo‐chitooligosaccharides (LCOs). The latter are also produced by nitrogen‐fixing rhizobia to induce nodules on leguminous roots. However, host enzymes regulating structure and levels of these signals remain largely unknown. Here, we analyzed the expression of a β‐N‐acetylhexosaminidase gene of Medicago truncatula (MtHEXO2) and biochemically characterized the enzyme. Muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 100 publications
0
0
0
Order By: Relevance
“…It is worth mentioning in this context that M. truncatula mutants carrying a Tnt1 retrotransposon in a β-N-acetylhexosaminidase gene (MtHEXO2) exhibit reduced colonization by AM fungi. MtHEXO2 is an extracellular enzyme that releases N-acetylglucosamine from fungal chitooligosaccharide signals [69]. Future research will reveal whether MtMFS1 and MtMFS2 are N-acetylglucosamine transporters and whether they are required for the establishment of AM symbiosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning in this context that M. truncatula mutants carrying a Tnt1 retrotransposon in a β-N-acetylhexosaminidase gene (MtHEXO2) exhibit reduced colonization by AM fungi. MtHEXO2 is an extracellular enzyme that releases N-acetylglucosamine from fungal chitooligosaccharide signals [69]. Future research will reveal whether MtMFS1 and MtMFS2 are N-acetylglucosamine transporters and whether they are required for the establishment of AM symbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, pISV2678, a binary vector with a Bar gene, was found to be very effective for the A. tumefaciens-mediated transformation of M. truncatula leaf explants [41,[67][68][69]. We therefore aimed to construct a CRISPR/Cas9 vector with a pISV2678 backbone and a DsRed1 expression cassette for the visual confirmation of transformants.…”
Section: Construction Of Crispr/cas9 Binary Vectors Suitable For M Tr...mentioning
confidence: 99%